An investigation and a simulation approach a border effects between Canada and United States - Kong, Jing (Université d'Ottawa | University of Ottawa, 2003)
After the Canada-US Free Trade Agreement and North American Free Trade Agreement were signed. Trade flows between Canada and the US increase substantially. The integration between the two countries was thought to be extremely high and border not mattered